PRACTICES OF RELIGIOUSNESS IN THE DOMESTIC AND FAMILY WORLD. SANTIAGO, 18TH CENTURY: THE RELIGIOUS IMAGES “FOR WHICH THEY REPRESENT” AND ¿HOW THEY ARE SHOWED? - Zamorano Varea, Paulina (Revista de Historia Social y de las Mentalidades, 2011)
This work is oriented to explain a religious practice, which was the possession of images, and to understand the importance and sense of the resource to the images of saints, holy and Christian devotions in the domestic imaginary of the 18th century. Toward the middle of the 18th century, the imaginary program enters in a process of tension with the norm, in the dispute by the meaning of the religious images for the Church and the faithful. In this century the ecclesiastical speech on the images tends to position them in its origin, to purify its objective by means of the control of its effects in the populace and the mob, control that operates connoting of indecent the meetings, the festivals and every action that desecrated to the image.